The Escalation of Systemic Risk: How Unrealistic KPIs and Organizational Misreporting Drive Moral Disengagement & Breeds Tolerance for Fraud - Yau, Yann Chuan (INTI International University, 2025)
This conceptual paper proposes a model in which aggressive Key Performance Indicators (“KPI”) and engaging in Low-Stakes Organizational Misreporting (“L-SOM”) results in Moral Disengagement (“MD”), which in turn leads to Tolerance for Fraud (“TF”) via. Aggressive KPIs promote short-term goal achievement at the expense of compliance with ethical standards (Thomas & Uminsky, 2022). Simultaneously, when employees partake in L-SOM, they activate the self-serving cognitive mechanisms of MD which contribute to the 'slippery slope' of corruption and the perpetuation of a systemic culture tolerant of fraud. (Moore, 2008). This paper draws on the Fraud Triangle and Social Cognitive Theory (Petitta et al., 2021) as underpinning theories. The model hypothesizes that KPI Pressure Intensity (“IV 1”) and Engagement in L-SOM (“IV 2”) contributes towards MD (“MV”), which ultimately impacts TF (“DV”). Data will be collected via surveys from employees, measuring their perception towards the various variable using a Likert scale. This study is innovative since it focuses on a situational, managerially produced environment rather than human deviance as the main cause of fraud vulnerability. Specifically, it establishes that IV 1 and IV 2 are two distinct and necessary inputs that jointly contribute to the decay of ethical thresholds through MD. It hypothesizes that: 1) KPI Pressure will positively predict MD; 2) Engagement in L-SOM will positively predict MD; and 3) MD will mediate the effect of both IVs on TF. This paper contributes to the study of organizational behavioural and fraud prevention by theorizing that unsustainable goals and the need to project unrealistic positive results result in an increased systemic risk of organizational fraud. It argues that the true risk of a flawed performance management system is not the initial compliance breach, but its role in training employees to rationalize wrongdoing. This framework serves as a vital foundation for future empirical research aimed at developing interventions to halt the moral disengagement process, thereby reducing systemic risk across industries